Implementasi Gerakan Respon Diare pada Balita di Kecamatan Jejawi Kabupaten Ogan Komering Ilir - Andarini, Desheila; Novrikasari, Novrikasari; Lestari, Mona; Yeni, Yeni (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2021)
The cause of diarrhea in infants and children is different from adults. In children, it is usually caused by a virus, whereas in adults it is caused by bacteria. Diarrhea in adults can be triggered by several factors, for example due to wrong eating, impaired digestion of food, the influence of drugs and due to psychiatric conditions whereas in infants can be infected if, swallowing these germs when passing through the birth canal is affected by germs or when touched by a hand germic. Children are also easily infected by germs because they often put their dirty hands and toys into their mouths. This research is a quantitative study in which the dependent variable data collection is done once at a time. The population in this study were all mothers of children under five in Talang Cempedak Village, Jejawi District, Ogan Komering Ilir Regency in 2019. The sample in this study were all toddler mothers in Talang Cempedak Village, Jejawi District, Ogan Komering Ilir Regency in 2019 by 18 people using total sampling technique. The results of this study from 18 respondents showed that 10 respondents amounted to 55.6% poor mother of toddler knowledge, as well as the behavior of 9 mothers of toddlers 50.0% bad and 50.0% good, and environmental sanitation in Talang Cempedak Village as many as 55.6 bad%. The  action in order to increase the movement to prevent diarrhea response in infants, such as counseling about diarrhea by health workers is needed so that the incidence of diarrhea can be prevented. Keywords: Diarrhea, Ogan Komering Ilir, Jejari, Counseling